PRODUCTION AND CHARACTERIZATION OF ANTI-LEUKAEMIC L-ASPARGINASE FROM NATIVE BACILLUS SP. - ZAHRA HOSSEINPOUR FEIZI; ARMIN ERAGHI KAZZAZ (International Journal of Pharma and Bio Sciences, 2016)
The enzyme L-asparaginase has received great attention as an antitumor agent for its treatment of tumor cells, particularly acute lymphoblastic leukemia. Additionally, as a food processing aid, L-asparaginase can significantly reduce the level of acrylamide in starchy foods. In this study, L-asparaginase was procured from soil isolates. The highest L-asparaginase producing strain was identified as Bacillus subtilis.The optimum activity of the purified enzyme was observed at 40 oC, at pH 8. In treating the enzyme with different buffers of pH, 100% of the stability was obtained at pH 7.0. By pre-incubating the enzyme at 20 oC to 100 oC, it was 100% stable at 50 oC, whereas the enzyme became unstable at temperatures over 70 oC. While urea and EDTA greatly decreased the enzyme activity, however, MgCl2 increased the activity. The enzyme was seen to be a single band with a molecular weight of 128 kDa by using the zymogram method.